تطبيق وسيلة التعليم "أدوبي فلاش" في ترقية مهارة الكلام - Hanifah, Umi; Dimyati, Afifuddin; Amaliyah, Nur Risma; Aprilia, Linda (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
The study entitled "Using Adobe Flash Learning Media to Improve Students' Arabic Speaking Skills" is motivated by the assumption that Adobe Flash learning media is suitable for improving students' Arabic speaking skills, because this learning media requires students to play an active role in learning activities. This study is in the form of a qualitative descriptive. Data collection methods used are: observation, interviews, and document analysis. The results of the study show that the application of Adobe Flash learning media can be used to improve students' Arabic speaking skills.